2017
DOI: 10.1177/0733464817709532
|View full text |Cite
|
Sign up to set email alerts
|

The Virtual Short Physical Performance Battery: Psychometric Properties and Validation in Older Adults With Multiple Sclerosis

Abstract: This report provides evidence for the validity of vSPPB scores as a measure of perceived lower extremity physical function in older adults with MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…The majority of these studies had floor and ceiling effects greater than the 15% of participants with floor and ceiling effects recommended by Portney and Watkins14 and the 20% deemed acceptable by Blum and Korner-Bitensky 41. A maximum score (12/12) was reported for 55.2% of a community-dwelling sample,40 2.9% of participants with multiple sclerosis and 34.3% of healthy controls 30. A minimum score (0/12) was reported in hospital settings (12%16; 39%17).…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…The majority of these studies had floor and ceiling effects greater than the 15% of participants with floor and ceiling effects recommended by Portney and Watkins14 and the 20% deemed acceptable by Blum and Korner-Bitensky 41. A maximum score (12/12) was reported for 55.2% of a community-dwelling sample,40 2.9% of participants with multiple sclerosis and 34.3% of healthy controls 30. A minimum score (0/12) was reported in hospital settings (12%16; 39%17).…”
Section: Resultsmentioning
confidence: 94%
“…41 A maximum score (12/12) was reported for 55.2% of a community-dwelling sample, 40 2.9% of participants with multiple sclerosis and 34.3% of healthy controls. 30 A minimum score (0/12) was reported in hospital settings (12% 16 ; 39% 17 ). Two studies noted low mean scores of 2.8 in patients with dementia in a geriatric hospital 19 and 2.0 on admission to hospital.…”
Section: Floor and Ceiling Effectsmentioning
confidence: 98%
See 2 more Smart Citations
“… 10 Previous studies among older adults without cancer have shown the virtual SPPB is valid, reliable, and moderately correlated with the in-person SPPB (correlation coefficient, r = 0.60-0.69). 10 , 11 …”
mentioning
confidence: 99%